Validity and Reliability of Mathematics Motivation Questionnaire - Adella Irma Wiyanti; Ariyadi Wijaya (Prodi Pendidikan Matematika STKIP Persada Khatu;istiwa Sintang, 2026)
This study aims to examine the validity and reliability of a mathematics motivation instrument using Microsoft Excel and Winsteps. This study employed a quantitative approach using a survey method. The participants were 136 students from a high school in Jakarta (grade XI) and a high school in Tangerang (grade X). Data analysis was conducted using the Rasch model and Microsoft Excel. The results indicated that 65 respondents exhibited misfit, as they did not satisfy the Outfit Mean Square (MNSQ), Outfit Z-Standard (ZSTD), and Point Measure Correlation (PTMEA-CORR) criteria, based on responses to 19 items. Furthermore, 71 students (52.2%) met the recommended criteria, while 65 students (47.8%) needed to be excluded, Cronbach's alpha (KR-20) value is 0, 90, the person's confidence value is 0.86 and the item's confidence value is 0.93. Furthermore, Validity test results using Microsoft Excel show calculation results of question items showing r_count>r_table where all question items are valid. Then the mathematical motivational instrument is said to be valid and has high reliability which has been verified and tested using the Winsteps and Microsoft Excel.Keyword: Mathematics Motivation; Validity; Reliability.